Medicolegal Handling Strategy For Sexual Violence Against Women at Sultan Agung Islamic Hospital Semarang - Dian Novitasari; Karli, Karli; Jamiatur Robekha (Sean Institute, 2025)
Sexual violence against women in Indonesia is an important issue that must be raised to be handled properly. In 2024, Komnas Perempuan recorded 445,502 cases of complaints of violence against women in Indonesia. Various factors behind it. However, this problem is still not of public attention until now. It even tends to be isolated so that it does not become public consumption. The majority of victims of gender-based violence are women and children. Women are vulnerable to violence because they are weak and powerless, as a result of unfair and equal gender relations. Men tend to be dominant in gender relations. This phenomenon can be seen in various data both in the media and social institutions that have concerns about handling this case. The qualitative study consisted of a normative approach, field observation and in-depth discussion (focus group discussion) to find out how the medicolegal strategy for handling sexual violence against women at the Sultan Agung Islamic Hospital in Semarang. The need for comprehensive, impartial and effective medicolegal handling needs to be applied in handling cases of sexual violence against women.